Pengaruh Risk Profile dan Net Interest Margin terhadap Kinerja Keuangan Perbankan Konvensional - Maylani Putri Indriyani; Ifan Wicaksana Siregar (Ekonomis: Journal of Economics and Business, 2026)
This study aims to analyze the effect of risk profile and net interest margin on financial performance in conventional banking companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. Risk profile in this study is proxied by the loan to deposit ratio (LDR), while financial performance is proxied by return on assets (RoA). The method used is a quantitative approach with multiple linear regression analysis techniques. Data collection was carried out using the documentation method on annual financial reports of 135 observations. The regression results show that simultaneously there is a significant influence between the risk profile and net interest margin variables on financial performance, but partially, the risk profile variable has a negative and insignificant effect, while the net interest margin variable has a positive and significant effect on financial performance in conventional banking companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023.